Avaliação externa dos cursos de graduação do Centro de Educação da Universidade Federal da Paraíba: da análise dos relatórios às propostas de melhoria dos cursos - Vieira, Tales Társis Dantas (2022)
This dissertation had as general objective to analyze if the Undergraduate Courses of the Education Center (CE) of the UFPB, according to the reports available on the website of the Assessment Committee (CPA), meet the guidelines established by SINAES. The present investigation was characterized as an applied research regarding its nature and has a qualitative approach, assuming an exploratory character regarding the outlined objectives. Bibliographic and documentary research were used as a procedure. The theoretical basis was supported by studies by José Dias Sobrinho, Valdemar Sguissardi, Graça Guerra, among other authors relevant to the study of the theme. In addition, the specific legislation on the evaluation of Higher Education in Brazil was the basis for the development of this study. For the analysis of course reports, a standard was established and the Undergraduate Course Assessment Instrument (IACG-2017) was used. SWOT analysis was also used to carry out the diagnosis, in order to know the internal environment of the organization through the definition of its strengths and weaknesses in relation to others that positively or negatively impact the quality of education both within the EC and in the UFPB, as well as in the external environment. For this investigation, the concept of quality proposed by SINAES was adopted. The research found that, in general, the courses evaluated are promising and likely to improve the results in the next evaluation, after all, dimensions 1 and 2 are potentialities, unlike 3. The results of the present study also supported the elaboration of proposals for action, based on the weaknesses and threats listed, with the intention of providing course managers with complementary knowledge to assist them in decision-making for the realization of the new demands of the IACG, aiming to improve the quality of the evaluation process in the face of the future evaluations for the renewal of recognition of the courses.